Differential functional readthrough over homozygous nonsense mutations contributes to the bleeding phenotype in coagulation factor VII deficiency. (19th September 2016) - Branchini, A.; Ferrarese, M.; Lombardi, S.; Mari, R.; Bernardi, F.; Pinotti, M.
Abstract : Essentials Potentially null homozygous Factor(F)7 nonsense mutations are associated to variable bleeding symptoms. Readthrough of p.Ser112X (life‐threatening) and p.Cys132X (moderate) stop codons was investigated. Readthrough‐mediated insertion of wild‐type or tolerated residues produce functional proteins. Functional readthrough over homozygous F7 nonsense mutations contributes to the bleeding phenotype. Summary: Background: Whereas the rare homozygous nonsense mutations causing factor (F)VII deficiency may predict null conditions that are almost completely incompatible with life, they are associated with appreciable differences in hemorrhagic symptoms. The misrecognition of premature stop codons (readthrough) may account for variable levels of functional full‐length proteins. Objectives: To experimentally evaluate the basal and drug‐induced levels of FVII resulting from the homozygous p.Cys132X and p.Ser112X nonsense mutations that are associated with moderate (132X) or life‐threatening (112X) symptoms, and that are predicted to undergo readthrough with (132X) or without (112X) production of wild‐type FVII. Methods: We transiently expressed recombinant FVII (rFVII) nonsense and missense variants in human embryonic kidney 293 cells, and evaluated secreted FVII protein and functional levels by ELISA, activated FX generation, and coagulation assays. Results: The levels of functional FVII produced by p.Cys132X and p.Ser112X mutants (rFVII‐132X, 1.1% ± 0.2% of wild‐type rFVII; rFVII‐112X, 0.5% ± 0.1% of wild‐type rFVII) were compatible with the occurrence of spontaneous readthrough, which was magnified by the addition of G418 – up to 12% of the wild‐type value for the rFVII‐132X nonsense variant. The predicted missense variants arising from readthrough abolished (rFVII‐132Trp/Arg) or reduced (rFVII‐112Trp/Cys/Arg, 22–45% of wild‐type levels) secretion and function. These data suggest that the appreciable rescue of p.Cys132X function was driven by reinsertion of the wild‐type residue, whereas the minimal p.Ser112X function was explained by missense changes permitting FVII secretion and function. Conclusions: The extent of functional readthrough might explain differences in the bleeding phenotype of patients homozygous for F7 nonsense mutations, and prevent null conditions even for the most readthrough‐unfavorable mutations.